Dampak Pemeliharaan Kebersihan Gigi dan Mulut terhadap Oral Health Related Quality of Life pada Anak dengan Autism Spectrum Disorder: Persepsi Orang Tua - Ika Anisyah; Roosje R. Oewen; Tuti Alawiyah; Rini Triani (e-GiGi, 2023)
Abstract: Autism spectrum disorder (ASD) children have disturbances in communication, social inter-action, and behavior that limit them from doing simple self-care, such as maintaining dental and oral hygiene. This study aimed to explain the impact between dental and oral hygiene maintenance on Oral Health Related Quality of Life (OHRQoL) in ASD children. This was an analytical and observational study with a cross sectional design. Samples were 65 parents/caregivers from the LRD Member Suar Autism community obtained by using purposive sampling. The questionnaire used for OHRQoL was the Fransiscan Hospital Oral Health Related Quality of Life (FHC-OHRQoL), and the dental and oral care questionnaire was in the form of Google form. The relationship between oral hygiene maintenance and OHRQoL was analyzed using the Kendall's Coefficient of Concordance correlation test and the Spearman Rank test. The results showed that the association between oral hygiene maintenance and OHRQoL as a whole was 97.1% (p<0.05). The relationship between OHRQoL domains (oral symptoms, children's daily life and parental attention) was 92.8% (p<0.05). The strongest correlation between oral symptoms and children's daily life was 65.61%. In conclusion, maintenance of oral hygiene as a whole has a high impact on OHRQoL, with a strong relationship between the OHRQoL domains, and children's daily life was the most influential one on oral symptoms. Keywords: dental and oral hygiene maintenance; OHRQoL; ASD children; parental perseption   Abstrak: Anak dengan autism spectrum disorder (ASD) memiliki gangguan berkomunikasi, berinteraksi sosial, dan berperilaku yang membatasinya antara lain dalam memelihara kebersihan gigi dan mulut. Penelitian ini bertujuan untuk menjelaskan dampak pemeliharaan kebersihan gigi dan mulut terhadap Oral Health Related Quality of Life (OHRQoL) anak ASD. Jenis penelitian ialah observasional analitik dengan desain potong lintang. Teknik pengambilan sampel menggunakan pusposive sampling. Jumlah sampel sebesar 65 orang tua/pengasuh dari komunitas LRD Member Suar Autism. Kuesioner penilaian OHRQoL yaitu The Fransiscan Hospital Oral Health Related Quality of Life (FHC-OHRQoL), dan kuesioner pemeliharaan gigi dan mulut dalam bentuk Google form. Keterkaitan pemeliharaan kebersihan gigi dan mulut dengan OHRQoL dianalisis menggunakan uji korelasi Kendall's Coefficient of Concordance dan Spearman Rank. Hasil penelitian mendapatkan keterkaitan pemeliharaan kebersihan gigi dan mulut dengan OHRQoL secara keseluruhan sebesar 97,1% (p<0,05). Keterkaitan domain OHRQoL (gejala oral, kehidupan sehari-hari anak dan perhatian orang tua) 92,8% (p<0,05). Keterkaitan paling kuat gejala oral dengan kehidupan sehari-hari anak 65,61% (p<0,05). Simpulan penelitian ini ialah pemeliharaan kebersihan gigi dan mulut secara keseluruhan berdampak besar terhadap OHRQoL, dengan keterkaitan yang besar di antara domain OHRQoL. Kehidupan sehari-hari anak ASD yang paling berpengaruh terhadap gejala oral. Kata kunci: pemeliharaan kebersihan gigi dan mulut; OHRQoL; anak ASD; persepsi orang tua